DOES WRITING ANXIETY IN GEN Z LEARNERS PREDICT SHARP PRACTICES IN ASSESSMENT? - Frank Ukofia , Id-Basil (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2023)
In Nigeria, English is arguably the most crucial subject in classrooms nationwide. Learning English as a second language has been difficult in Nigeria. This is true across all four skills (listening, reading, and writing). Indeed, the difficulty of mastering written English is a stumbling block to expanding learning opportunities and potentiates the incident of sharp practices in academia. The present study examined the correlation between writing anxiety and sharp practices in assessments among young learners. One hundred eighty-seven undergraduates enrolled in various courses at the Federal College of Education Technical, Omoku, River state, participated in the study. A correlational research design was adopted, and the result indicated a positive correlation between writing anxiety and academic dishonesty. The study concludes that writing anxiety significantly determines cheating in undergraduates